Alarbaeen Pilgrimage: A Reading in Light of Cultural Criticism - Ruaa Abdul Jawad Lafta; M.M. Hawraa Hadi Kadhim (Peerian Journals Publishing, 2025)
The research presents an interactive reading of the Alarbaeen Pilgrimage in light of cultural criticism, describing it as a cultural phenomenon with two dimensions: semantic and symbolic, intertwined with religious, social, and political dimensions. Through it, the values and principles associated with the revolution of Imam Hussein (peace be upon him) are evoked and transformed into living practices that influence the collective consciousness. Furthermore, it serves as spiritual nourishment, encompassing feelings of grief, spiritual and psychological purification, and a return to the human self
Keywords: Alarbaeen; Alarbaeen Cultural Criticism